Emotional Intelligence and Its Role in Business Communication (MMIT Proceedings, 2024)
The article examines the role of emotional intelligence (EQ) in the workplace and its influence on organizational efficiency and employee success. It describes the concept of emotional intelligence proposed by John Mayer and Peter Salovey, as well as its key characteristics such as self-awareness, self-regulation, empathy, motivation, and social skills. The ways to improve emotional intelligence in the workplace are explored.